AN OVERVIEW ON MANAGING CHANGES FOR BANK RISKS IN TIMES OF FINTECH (R)EVOLUTION: A CHALLENGE OR OPPORTUNITY? - Bedjeti Baftijari, Artina; Nakov, Leonid (Faculty of Economics-Skopje, SS. Cyril and Methodius University in Skopje, 2020)
Most of the economic activities are becoming highly digital. In the past several years changes in the technological improvements and financial innovations had an enormous impact on the modern financial system. Worldwide, the banking industry has changed and integrated the financial technology (FinTech) in its everyday routine. Nowadays, for some financial members FinTech provides a big threat and a challenge for the traditional banking, while for some others it provides an opportunity for more flexibility, better service functionality and higher service quality. Overall, banks adopt innovations to satisfy customers’ demands, despite the risks and challenges imposed from FinTech and new financial product development (NFPD). In general banks benefit from opportunities of the new product development in the aspect of allocating more efficiently the resources, reduction in transaction costs, promotion, revenue growth and profitability. The aim and objective of this paper is to identify and evaluate the main risks related to development of FinTech and financial innovations that banks are exposed to (on micro and macro level), and to provide recommendations on the reduction of those risks and controlling them. Based on literature review, researches proved that one of the major obstacle to firm`s innovativeness is the negative impact of the new financial product development on banking risks. It is recommended that in times of technological boom commercial banks should invest their available funds in suitable techniques for successfully accepting new financial product development.
Keywords: FinTech; Financial innovation; Managing changes; Commercial banks; New financial product development